(untitled) (Anclajes, 2025)
Disco magazine (1945-1947), directed by Juan Rodolfo Wilcock, has been described by literary critics as being removed from the literary and political controversies of its time. However, it is possible to connect its neo-romantic orientation with an anti-Peronist political position. Faced with what it perceived as a terminal crisis of civilization, the poetry of the 1940s generation adopted an elegiac tone and proposed a restoration of classical forms. In the politicization of the literary field at the time, the Neo-romantics were part of the liberal or anti-fascist camp, which from 1945 became anti-Peronist. An analysis of the magazine covers and the selection of foreign texts demonstrates that Disco combines the poetics of the cuarentistas, which pre-dated Peronism, with an anti-Peronist cultural project. This affinity goes beyond Wilcock’s personal connections, and is due to the specific characteristics of Neo-romanticism.